A study on the leadership style influence to achieve readiness to change among employees in UDA Land (South) Sdn. Bhd. Johor Bahru / Puteri Suraya Khalid - Khalid, Puteri Suraya (2010)
Changes often occur around the world, no matter the time changes, weather, technology, finance, management and others. Organization regardless of the government and private sectors are also facing changes due to changes in the organization is able to measure the dependability and resilience of the organization survival in the industry. Changes to be made to ensure the organization continues to achieve a higher limit. Although the organization has reached the desired level, minor changes will be implemented to remain in his remarkable and challenging for other organizations. Change can give major impact to the employees in one company. This study provides an analysis regarding the leadership style which can influence the readiness to change among the employees and one organization. The main objective on this project paper is to study the level of readiness to change on employees in UDA Land (South) Sdn Bhd (ULSSB). The study also will indicate the strength of association between variables. This research is focusing on the employees at ULSSB and takes 49 staff as respondents since the populations in ULSSB are 49 people. In addition, the theoretical framework of this research consists of dependent variable; readiness to change and independent variable, independent variable; autocratic style, democratic style and laissez- faire style. There are lots of suggestions from this study and might be useful for future improvement.